2014
DOI: 10.1097/bot.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Macrophage Activity During Fracture Repair Has Differential Effects in Young Adult and Elderly Mice

Abstract: Objectives Advanced age is a factor associated with altered fracture healing. Delays in healing may increase the incidence of complications in the elderly, who are less able to tolerate long periods of immobilization and activity restrictions. The following study sought to determine if fracture repair could be enhanced in elderly animals by inhibiting macrophage activation, blocking the M-CSF receptor c-fms, and inhibiting monocyte trafficking using CC chemokine receptor-2 (CCR2) knockout mice. Methods Close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Similarly, another study reported that macrophages in aged mice secreted lower levels of pro-angiogenic factors than macrophages from young mice, resulting in impaired wound healing [125]. In addition, inhibiting M-CSF receptor kinase activity reduced macrophage numbers and induced a trend of increased bone formation in old but not young mice [126]. These data indicate that the function of macrophages may change with age, and thus age and other contextual factors should be considered when designing macrophage-targeted approaches.…”
Section: Unresolved Questions: Obstacles and Opportunitiesmentioning
confidence: 99%
“…Similarly, another study reported that macrophages in aged mice secreted lower levels of pro-angiogenic factors than macrophages from young mice, resulting in impaired wound healing [125]. In addition, inhibiting M-CSF receptor kinase activity reduced macrophage numbers and induced a trend of increased bone formation in old but not young mice [126]. These data indicate that the function of macrophages may change with age, and thus age and other contextual factors should be considered when designing macrophage-targeted approaches.…”
Section: Unresolved Questions: Obstacles and Opportunitiesmentioning
confidence: 99%
“…Consequently, cautious but optimistic progression of this therapeutic avenue is justified. Additional remaining questions include whether perturbations in macrophage function and/or subset dominance underlie impaired fracture healing or systemic bone disease, including bone fragility associated with chronic inflammation, infection, anti‐inflammatory treatment, and age …”
Section: Osteal Macrophages Are Key Regulators Of Osseous Wound Healingmentioning
confidence: 99%
“…179 The recruitment of inflammatory cells to sites of injury is mediated by four different subfamilies of chemokines (CC, CXC, CX3C and C) based on their biochemical, structural and functional properties 180 . In a Ccr2 −/− mouse model of decreased macrophage recruitment, it was shown that disruption of Ccr2 signaling impaired vascularization, decreased formation of callus, and delayed maturation of cartilage and bone remodeling up to 21 days after injury 181,182 . M2 macrophages contribute to the resolution of inflammation and are important to the progression bone healing.…”
Section: Role Of Stem Cells In Vascularized Bone Regenerationmentioning
confidence: 99%
“…Dysregulation of macrophage polarization, specifically persistence of the M1 phenotype or dampened M2 response, may contribute to age related delays in bone healing. 180182 …”
Section: Role Of Stem Cells In Vascularized Bone Regenerationmentioning
confidence: 99%